Chapter Massimo Quaini: la Liguria labirinto e laboratorio - Gemignani, Carlo Alberto (Territori, 2021)
Liguria was the great 'action scenario' for Massimo Quaini. A region that, thanks to historical and environmental conditions, allowed him to read in advance phenomena and dynamics that would later occur at a national scale. This contribution does not pretend to exhaust the substance of a relationship that goes beyond the scientific level and involves deep existential bonds, but only to provide some elements to draw a first map of the scientific reasons that have linked the scholar to his land of belonging. This reflection will hopefully serve to define how much Liguria is found in Massimo Quaini's geographical thinking and how much the Ligurian society should still make use of the sharp portraits the scholar has been able to dedicate to her.